Transcriptomic Profiling of MSI-H/dMMR Gastrointestinal Tumors to Identify Determinants of Responsiveness to Anti–PD-1 Therapy - Chida, Keigo; Kawazoe, Akihito; Suzuki, Toshihiro; Kawazu, Masahito; Ueno, Toshihide; Takenouchi, Kazumasa; Nakamura, Yoshiaki; Kuboki, Yasutoshi; Kotani, Daisuke; Kojima, Takashi; Bando, Hideaki; Mishima, Saori; et al. (Clinical cancer research, 2022)
Transcriptomic profiling was performed for microsatellite instability-high (MSI-H)/mismatch repair-deficient (dMMR) gastrointestinal tumors to determine the predictors of response to PD-1 blockade. Thirty-six patients with MSI-H/dMMR gastrointestinal tumors, including gastric cancer, colorectal cancer, cholangiocarcinoma, small intestine cancer, and pancreatic cancer, being treated with PD-1 blockade were analyzed. We conducted the transcriptomic analysis of gastrointestinal tumors using RNA sequencing data, including the consensus molecular subtypes (CMS) of colorectal cancer. Gene set enrichment analysis (GSEA) demonstrated that non-responders had upregulations of epithelial-mesenchymal transition, angiogenesis, hypoxia, mTORC1, TNF-α, KRAS, Wnt/β-catenin, TGF-β, and various metabolism-related signaling pathways. Meanwhile, the IFNγ pathway was enriched in responders. On the basis of the leading-edge analysis of GSEA, VEGF-A was significantly correlated with enriched pathways in non-responders. Patients with high VEGF-A expression, compared with those with low expression, had significantly shorter progression-free survival [PFS; median 4.8 months vs. not reached (NR), P = 0.032] and overall survival (median 11.1 months vs. NR, P = 0.045). Among 13 patients with colorectal cancer evaluable for CMS classification, the objective response rate was 100%, 0%, 0%, and 16.7% in CMS1, CMS2, CMS3, and CMS4, respectively. Patients with CMS1 had significantly longer PFS (NR vs. 4.8 months, P = 0.017) than those with CMS2, CMS3, or CMS4. Several transcriptomic features, including CMS classification and related genes, were associated with response to PD-1 blockade in MSI-H/dMMR gastrointestinal tumors. These findings can help develop predictive biomarkers or combination immunotherapies.